Development of an E-Module Based on Integrated Scientific Literacy with Islamic Values in Chemical Equilibrium Material for SMA/MA - Anggraeni, Septi; Rahmawan, Setia (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Abstract : Developing an e-module based on scientific literacy integrated with Islamic values in chemical equilibrium material is a significant effort to improve students' scientific literacy skills and increase students' awareness of the spiritual aspect. Study This aims to develop an e-module based on scientific literacy integrated with Islamic values in chemical equilibrium material and analyze the quality and response of participants towards modules that were developed. Study This study uses the ADDIE development model. The ADDIE development model consists of 5 stages: analysis, Design, Development, Implementation, and Evaluation. However, in the study, This is limited until on-stage development. Research data was obtained from a validation sheet media expert, sheet validation expert material, chemistry teacher assessment sheet, and response education the e-module being developed. Validation was carried out by two expert lecturers, material experts, and media experts. The quality of the e-module was obtained through an assessment carried out by three chemistry teachers, and a result of 93.3% was obtained in the excellent category. Then, a trial was carried out on 30 students at SMA Muhammadiyah 3 Yogyakarta to determine the students' responses to the e-module being developed. The test results received a percentage score of 96% in the very positive category. This research shows that a module based on scientific literacy, integrated Islamic values in chemical equilibrium material, is very worth using in the learning process. Keywords: E-Module, Chemical equilibrium, Scientific literacy, Integration of Islamic Values. DOI: 10.23960/jppk.v13i1.29524